Cutaneous Anthrax In The Era Of Biodefense: Clinical Recognition, Biosurveillance, And Biosecurity Implications For Modern Health Care Systems — A Systematic Review - sausan maulida; Dian Andriani Ratna Dewi (Perkumpulan Kedokteran Militer, 2026)
Background: Cutaneous anthrax represents the most frequent clinical manifestation of Bacillus anthracis infection with dual threat as endemic zoonotic disease and potential bioterrorism agent, necessitating modern health systems to integrate proactive biosurveillance capabilities with robust biosecurity protocols for epidemiological and national security risk mitigation. Objective: To identify pathognomonic clinical characteristics and differential diagnostic algorithms, evaluate effectiveness of integrated biosurveillance platforms in detecting outbreak early warning signals, and formulate biosecurity implications for policy development and operational readiness of health facilities. Methods: Systematic literature review utilizing PubMed, Scopus, Web of Science, and Google Scholar databases covering 2015-2025 period with inclusion criteria of original research articles, systematic reviews, and clinical guidelines. Seven high-quality articles were analyzed using thematic narrative synthesis. Results: Identification of diagnostic complexity requiring laboratory confirmation through bacteriological culture or molecular testing, temporal gap in notification averaging 6.3 days, environmental pathogen persistence of 11.40% in soil samples, seroprevalence 9-11% in high-risk populations, and corticosteroid therapy efficacy in edema reduction (P<0.002). Conclusion: Optimization of clinical recognition through molecular diagnostic integration, strengthening biosurveillance architecture based on spatiotemporal One Health analysis, and formulation of responsive biosecurity policy represent essential pillars of preparedness against emergent biological threats. Keywords: Cutaneous Anthrax, Biosurveillance, Biosecurity